Lactational exposure to short-chain chlorinated paraffins in China, Korea, and Japan. (April 2017) - Cao, Yang; Harada, Kouji H.; Hitomi, Toshiaki; Niisoe, Tamon; Wang, Peiyu; Shi, Yuhui; Yang, Hye-Ran; Takasuga, Takumi; Koizumi, Akio
Abstract: To investigate short-chain chlorinated paraffin (SCCP) levels in human breast milk, pooled breast milk samples (BMSs) collected between 2007 and 2010 from Chinese (Beijing, n = 17), Korean (Seoul, Busan, n = 16), and Japanese (Kyoto, Sendai, n = 44) women were analyzed. SCCPs found in air samples in Beijing ( n = 4, in 2008) were also analyzed and compared with BMSs to estimate the possible source of contamination in Beijing. The electron-capture negative ionization method demonstrated the different sensitivities for SCCPs, and pentachlorinated alkanes had the highest method detection limit (MDL) among congeners. In Beijing, SCCPs were detected in 8 of 17 pooled BMSs at concentrations more than the highest MDL of each homolog. The total SCCP concentration ranged from below the MDL to 54 ng g −1 lipid weight. Among the SCCP homologs, polychlorinated tridecanes were most frequently detected in Beijing. In Korea and Japan, no samples contained detectable total SCCP concentrations at more than the highest MDL. In Seoul, only two samples showed trace levels of polychlorinated undecanes. In Kyoto and Sendai, congeners of polychlorinated dodecanes were most frequently detected. C10 components were the major contributors to the SCCPs in the atmosphere of Beijing. Congener profiles in breast milk in Beijing provided a clear contrast to the profiles found in food and air. The unique congener profiles necessitate the monitoring of breast milk for exposure of infants to SCCPs. The calculated mean exposure of SCCPs in 1-year-olds in China was 337 ng (kg body weight) −1 d −1 . These results demonstrate the body burden of SCCPs in the study areas and potential lactational exposure to SCCPs in Asian countries. Highlights: SCCPs were detected in breast milk collected from several cities in East Asia. Concentration of SCCPs in breast milk (in ng g −1 lipid weight) was <20–54. The mean exposure of SCCPs in 1-year-olds in Beijing was 337 ng (kg body weight) −1 d −1 . This mean exposure value was significantly higher than those for Korea and Japan. Breast milk SCCP content from Beijing differed from that in ambient air and food.